2018
DOI: 10.1007/s10549-018-4676-3
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant hormonal therapy for early breast cancer: an epidemiologic study of medication adherence

Abstract: Non-adherence is a common, complex, and multidimensional healthcare problem. This better understanding and knowledge of risk factors will allow healthcare providers (such as oncologists, general practitioners, pharmacists) to more easily identify patients at risk for non-adherence and help them provide appropriate information about AHT and its management, thus improving medication adherence in their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
3
25
1
2
Order By: Relevance
“…For patients with HR+ (estrogen and/or progesterone) disease, the National Comprehensive Cancer Network (NCCN) recommends initiating hormonal therapy (HT) regardless of lymph node status, age, or whether chemotherapy is initiated . Given the established efficacy and favorable side effect profile, adjuvant HT is widely used to reduce disease relapse and breast cancer mortality, as well as improve disease‐free survival . Clinical trials have demonstrated that HT decreased the 5‐year and 10‐year breast recurrence rates while extending HT to 10 years further improves disease‐free survival …”
Section: Introductionmentioning
confidence: 99%
“…For patients with HR+ (estrogen and/or progesterone) disease, the National Comprehensive Cancer Network (NCCN) recommends initiating hormonal therapy (HT) regardless of lymph node status, age, or whether chemotherapy is initiated . Given the established efficacy and favorable side effect profile, adjuvant HT is widely used to reduce disease relapse and breast cancer mortality, as well as improve disease‐free survival . Clinical trials have demonstrated that HT decreased the 5‐year and 10‐year breast recurrence rates while extending HT to 10 years further improves disease‐free survival …”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported high as well as low rates of adherence. 2,3,5 In our study, most participants reported that they had received information on the importance of ET, but interestingly, this information was mostly from their physicians rather than pharmacists. We found no association between the high adherence and the information provided by physicians which might be due to the nature of the study as there was no objective measure of the physician's role in patient's counseling.…”
mentioning
confidence: 63%
“…The questionnaire was developed by a survey specialist at our institution since, to our knowledge, there was no validated, well-established questionnaire in Arabic. The questionnaire contained items that were reported by Pourcelot et al 2 The questionnaire included questions on adherence (the number of missed doses of ET during the previous month) and type and duration of ET, perception about ET. The survey specialist and the clinical investigators assessed the items in term for clarity and relevance for the patients to establish the face and content validity of the questionnaire.…”
mentioning
confidence: 99%
“…Suggesting that 'patients should be educated' about the necessity of adhering to prescribed medication seems not to be very productive [40,49]. One might even make the case, consistent with the analyses in the WHO report on Adherence, that it is not the patient but rather the health care provider who should be educated about adherence as a complex aspect of human behavior.…”
Section: Discussionmentioning
confidence: 99%